(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
Over the last two decades, the platformization of viewing practices has transformed patterns of circulation, multiplying the possibilities for engagement with cinema: not only new viewing spaces themselves but also vast amounts of readily accessible related content (trailers, publicity, clips, etc.). The aim of this essay is to consider how these changes have impacted the potential for popular European cinema—which has historically strayed little from each national domestic market—to travel abroad and outside of “traditional” contexts of consumption. We shed some light on this question by examining how content related to a handful of highly successful European films is used on YouTube, the most widespread and accessible repository of online videos. Following a discussion of the changes in the digital distribution sphere, we identify the most lucrative European films from the five largest film markets of the continent—France, UK, Germany, Italy, Spain—since the launch of YouTube. Isolating seven examples, we then trace out their presence on the platform, questioning what kind of content relating to the films is available; engagement rates with these videos; indicators of local and global consumption; and what these results can tell us about the spectatorship habits of European cinema today.